Electrical stimulation of the human brain: perceptual and behavioral phenomena reported in the old and new literature - Selimbeyoglu, Aslihan; Parvizi, Josef (Frontiers in Human Neuroscience, 2010)
In this review, we summarize the subjective experiential phenomena and behavioral changes that are caused by electrical stimulation of the cerebral cortex or subcortical nuclei in awake and conscious human subjects. Our comprehensive review contains a detailed summary of the data obtained from electrical brain stimulation (EBS) in humans in the last 100 years. Findings from the EBS studies may provide an additional layer of information about the neural correlates of cognition and behavior in healthy human subjects, or the neuroanatomy of illusions and hallucinations in patients with psychosis, and the anatomy of seizure signs and symptoms in patients with epilepsy. In addition to a comprehensive overview of published reports in the last hundred years, we discuss some of the fundamental concepts, issues, and remaining questions that have defined the field of EBS. We also review the current state of knowledge about the mechanism of action of EBS suggesting that the modulation of activity within a localized, but distributed, neuroanatomical network might explain the perceptual and behavioral phenomena that are reported during focal electrical stimulation of the human brain.